Patterns of Opioid Use for Chronic Non-Cancer Pain in the Veterans Health Administration from 2009 to 2011 - Edlund, Mark J. (Pain, 2014)
Although opioids are frequently prescribed for chronic non-cancer pain (CNCP) among Veterans Health Administration (VHA) patients, little has been reported on national opioid prescribing patterns in the VHA. Our objective was to better characterize the dosing and duration of opioid therapy for CNCP in the VHA. We analyzed national VHA administrative and pharmacy data for fiscal years 2009 to 2011. For individuals with CNCP diagnoses and any opioid use in the fiscal year, we calculated the distribution of individual mean daily opioid dose, individual total days covered with opioids in a year, and individual total opioid dose in a year. We also investigated the factors associated with being in the top 5% of individuals for total opioid dose in a year, which we term receipt of high volume opioids. About half of the patients with CNCP received opioids in a given fiscal year. The median daily dose was 21 milligrams morphine equivalents. Approximately 4.5% had a mean daily dose higher than 120 milligram morphine equivalents. The median days covered in a year was 115 to 120 days in these years for those receiving opioids. Fifty-seven percent had at least 90 days covered with opioids per year. Major depression and post-traumatic stress disorder were positively associated with receiving high volume opioids, but non-opioid substance use disorders were not. Among VHA patients with CNCP, chronic opioid therapy occurs frequently, but for the large majority of patients the average daily dose is modest. Doses and duration of therapy were unchanged 2009–2011.